Uji Validitas Media Papeda Berbasis Permainan Ular Tangga Untuk Meningkatkan Pemahaman Materi Bangun Datar Pada Siswa Kelas III Sekolah Dasar - Putri, Vera Zunita; Tabina , Melia Hansa Cordelia; Nisa , Sahda Aqila; Sanjaya, Elvona Agasthi Natarina; Fardani , Much Arsyad (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study aims to develop and test the feasibility of PAPEDA (Flat Shape Knowledge Board) learning media based on snakes and ladders game as a means to improve the understanding of third grade elementary school students on flat shape material. This study uses the Research and Development (R&D) method with the ADDIE development model consisting of five stages, namely: analysis, design, development, implementation, and evaluation. The subjects in this study were 10 third grade students of SD Negeri 2 Demaan and 1 class teacher. Validation was carried out by media experts and material experts, and practicality testing was carried out through student and teacher responses. Data collection techniques were carried out through expert validation and questionnaire distribution. The validation results showed that the media obtained a feasibility score of 90% from media experts and 92.5% from material experts with the category "very feasible". The data analysis technique was carried out descriptively quantitatively by calculating the percentage of scores from the validation sheets of media experts and material experts, then categorized into feasibility criteria. The results showed that the PAPEDA media was declared very feasible based on the results of the validation by media experts of 90% and material experts of 92.5%. Limited trials also showed the practicality of the media with student responses of 85% and teacher responses of 80%, both included in the "very practical" category. Limited trials showed a positive response from students of 85% and from teachers of 80% with the "very practical" category. Thus, the PAPEDA media was declared feasible and practical to be used in mathematics learning on flat shape material in grade III of elementary school.